Building Ahlus-Sunnah wal-Jamaah an-Nahdliyah Character as the Pillar of Islamic Moderation in Islamic Boarding School - Faris Khoirul Anam; Moh. Padil; Mokhammad Yahya (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This research aimed at identifying the Moslems character called Ahlus-Sunnah wal-Jamaah an-Nahdliyah (Aswaja) to strengthen the Islamic moderation in Islamic Boarding School. Islamic moderation became an important topic in developing the understanding of diversity in Indonesia. The mixed-method study depended on quantitative and qualitative data sourced from the questionnaire comprising three domains of knowledge, attitude, and the practice of Islamic moderation and in-depth interview with the students, alumni, teachers, and the leaders of Islamic Boarding School. Based on the result of unpaired t-test, the study found out that significance for the knowledge was 0.80, for the attitude was 0.03, for the practice was 0.46, while the total reached 0.36. It also unveiled that it necessary to strengthen the materials of Aswaja in building Aswaja-based Moslems characters in Islamic boarding schools. This study identified eight characters of Aswaja Moslems as the source of material and curriculum development for Islamic Moderation in Islamic Boarding School, including (1) Islamic moderation guidance; (2) the maintenance of togetherness; (3) the acknowledgment of the authorization of fiqh schools; (4) the existence of bid’ah hasanah; (5) the loyal opposition to leaders; (6) the non-liberal method; (7) non-dominance of the truth; (8) the respect to the local wisdom under the standard of ushul fiqh. This study expected to embody the spirit of religious moderation in Indonesia.